Spatial and seasonal distribution of frogs in three environments in the Serra do Ouro Branco, extreme south of Cadeia do Espinhaço, Minas Gerais, Brazil - Vinícius de Avelar São Pedro; Renato Neves Feio (Biotemas, 2010)
We provide information on the spatial and seasonal distribution of frog species in the Serra do Ouro Branco, south Cadeia do Espinhaço, Brazil, from the tracking of three aquatic environments: a pond, a permanent stream and a temporary stream, carried out between July 2006 and June 2007. We found 28 species belonging to the families Brachycephalidae (2), Bufonidae (2), Centrolenidae (1), Cycloramphidae (2), Hylidae (16), Leiuperidae (2), Leptodactylidae (2) and Microhylidae (1). The pond showed the greatest richness (20). Five different reproductive patterns were defined: (1) species that call year-round or almost year-round, with larger aggregations during rainy months, (2) opportunistic species with calling activity associated with the rainy months, (3) species that call predominantly in winter, (4) species with an explosive reproductive pattern, with peaks of calling activity during heavy rains, and (5) species that do not show a definite calling pattern. The reproductive activity of most species was shown to be associated with rainy months, but showed no link to the temperature. There was overlap in the seasonal distribution of some species. The spatial and seasonal species distribution seems to adapt to the biotic and abiotic factors of the environment occupied.